Infrastruktur, Investasi dan Implikasinya Terhadap Pertumbuhan Ekonomi: Kasus pada provinsi-provinsi di Pulau Jawa dan Luar Pulau Jawa - Astariadi Kurniawan; Muhamad Ihsan (Universitas Pasundan, 2021)
The economic impact of infrastructure has been a matter of debate for the past three decades. The provision of adequate infrastructure has been considered as one of the essentials of long-term economic growth and development. This study aims to test the hypothesis of the relationship between the variables studied, where the main variables that are the focus of the research are investment and infrastructure, while the control variables used are labor and government spending. The method used is a panel data regression model (Panel Pooled Data) because this study is a combination of cross-section and time-series data. The data used as a time series is during the period 2009-2018, while the cross-section data are all provinces in Indonesia which are grouped into provinces in Java Island and outside Java Island. The results of the study show a positive and significant influence on the investment and road infrastructure variables in the provinces on the island of Java and there is a positive and significant influence on the investment, labor, road infrastructure, and telecommunications infrastructure variables in provinces outside Java. Meanwhile, at the National level, there is a positive and significant influence on the variables of Investment, Manpower, and Road Infrastructure.